Agreement of different OCT scan directions for individual retinal-layer thickness measurements in multiple sclerosis subjects with prior unilateral optic neuritis - Domínguez-Vicent, Alberto; Nilsson, Maria; Brautaset, Rune; Venkataraman, Abinaya Priya (Scientific reports, 2022)
The similarities between horizontal and vertical Optical Coherence Tomography (OCT) scans for the individual retinal layer thickness measurements in the macula was evaluated. Two volumetric scans (B-scans oriented horizontally and vertically) were performed in 64 multiple sclerosis subjects with history of unilateral optic neuritis and 64 healthy controls. The agreement between the thickness measurements with horizontal and vertical OCT scans was evaluated in 3 groups of eyes: healthy controls, eyes with history of optic neuritis and the fellow eyes. The mean difference in individual layer thickness between the scans was smaller than the instrument’s axial resolution in all 3 groups. The limit of agreement (LoA) varied among the different layers and sectors analyzed and this trend was similar in all the groups. For the inner retinal layers (retinal nerve fiber layer to inner nuclear layer), the inner macular sectors had a larger LoA compared to the corresponding outer sectors. In the outer plexiform and nuclear layers, the central and inner sectors (except inner temporal) had LoA larger than the other sectors and layers. The larger LoA seen for different layers and sectors suggests that the scan direction must be same for the follow-up OCT measurements and in clinical studies.